Glass ceramics containing ferroelectric phases - Parkash O.; Kumar D.; Pandey L. (My University, 2025)
Glass ceramics prepared by controlled crystallization of glasses produce fine dispersion of crystallites in a glassy matrix. Glasses containing a mjor portion of constituents of a ferroelectric phase produce crystallites of ferroelectric phase in glass through a suitable heat treatment. The amount of network former in the initial glass has a profound influence on its crystallization behaviour and microstructure of the resulting ferroelectric glass ceramics. The value of dielectric constant and the nature of ferroelectric to paraelectric transition depend on the crystallite size and volume fraction of the ferroelectric phase. These glass ceramics are transparent for crystallite size less than 0·1 μm and exhibit large quadratic-electro-optic effect. © 1986 Indian Academy of Sciences.